Gerakan Tolak Proyek Reklamasi Teluk Benoa sebagai Penguatan Identitas Kultural Masyarakat Bali - Ni Wayan Rainy Priadarsini S.; Putu Ratih Kumala Dewi; A.A.A. Intan Parameswari (Jurnal Kajian Bali (Journal of Bali Studies), 2018)
From the beginning of its emergence, the Benoa Bay reclamation project that received fully support from Bali Provincial Government had been rejected by Balinese people in general. The project worked by PT Tirta Wahana Bali International is considered as a form of global capitalist hegemony. Thousand of demonstrators protested against the reclamation project because it is not only threatening the ecology sustainability but also the local culture. “Reject Reclamation” movement, organized by the Balinese People’s Forum to Reject Reclamation(ForBALI), as opposition to global capitalist control. It has been thirty nine customary villages in Bali protested in various ways against the controversial project. This article discusses the struggle of Balinese peopleto reject Benoa Bay’s reclamation plan through the revitalization of Balinese cultural identity to face the global capitalist hegemony.